EVALUASI KINERJA BURSA KERJA KHUSUS (BKK) SMK PGRI 1 SURAKARTA DENGAN MENGGUNAKAN MODEL CIPP - Widi Kisniantoro; Yuyun Estriyanto; Indah Widiastuti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2019)
The research based on the absence of assessment on the BKK performance in SMK PGRI 1 Surakarta. The objectives of the research are to evaluate: (1) The performance context of BKK including (a) objective of BKK, (b) duties and functions of BKK, (c) relevance of students needs; (2) The performance input of BKK including: (a) human resources, (b) infrastructure, (c) Standart Operational Procedure, (d) funding; (3) The performance process of BKK including: (a) Management of BKK, (b) student, (c) performance Barrier of BKK; (4) The performance product of BKK that is the achievement of BKK. This research was conduted in SMK PGRI 1 Surakarta. The Research employed qualitative evaluation Research method with CIPP (Context, Input, Process, Product) model. Respondents who become the data object of the Research is headmaster, 2 staff of BKK, 70 students in grade XII. Technique of collecting data used were questionnaire, interview and documentation. Data validation in his research was carried out by using logic validity. The interview was analyzed by using triangulation and The questionnarie was analyzed by using mean analysis which is assessed based on the assesment criteria. The result of the research show as follow: (1) evaluation of the context of BKK is adequate, (2) evaluation of BKK performance inputs is still low, (3) the evaluation of BKK performance process is good enough, (4) the evalution performance Products of BKK on aspects of achievement is still low.